Improving Teachers' Digital Literacy at SMP Islam Al-Atrawiyah Ganding Through Human Resource Development Training - Isma’il Isma’il; Ribut Wahyu Eriyanti; Hari Sunaryo (Electronic Journal of Education, Social Economics and Technology, 2025)
The current state of teacher literacy in Indonesia continues to face various challenges, ranging from limited conceptual understanding of literacy as a multidimensional construct to constraints in applying digital literacy in the learning process. Many teachers still interpret literacy narrowly as the ability to read and write, without linking it to critical thinking skills, reflective capacity, and proficiency in information technology-competencies that are essential in the 21st-century educational ecosystem. At SMP Islam Al-Atrawiyah Ganding, this issue has become a major focus in efforts to improve the quality of education based on Islamic values that are responsive to technological advancement. This study aims to enhance teacher literacy by strengthening their understanding of literacy in a comprehensive and contextual manner. The literacy in question includes pedagogical literacy, digital literacy, and values-based literacy (ethics and Islamic spirituality), all of which are integrated into teaching practices. The study employs a qualitative descriptive approach using participatory observation, in-depth interviews, and document analysis. Findings show that a deep conceptual understanding of literacy forms a crucial foundation for developing innovative and relevant teaching strategies. Teacher training that emphasizes the conceptual dimensions of literacy can improve reflective awareness, ICT skills, and commitment to educational transformation. This article recommends the formulation of school policies that focus on the continuous and collaborative strengthening of teacher literacy as a key to fostering an inclusive, critical, and transformative learning environment in the digital era.